Efficient boron abstraction using honeycomb-like porous magnetic hybrids: Assessment of techno-economic recovery of boric acid - Oladipo, Akeem Adeyemi; Gazi, Mustafa (Academic Press Ltd- Elsevier Science Ltd, 2016)
Porous magnetic hybrids were synthesized and functionalized with glycidol to produce boron-selective adsorbent. The magnetic hybrid (MH) comparatively out-performed the existing expensive adsorbents. MH had a saturation magnetisation of 63.48 emu/g and average pore diameter ranging from meso to macropores. The magnetic hybrids showed excellent selectivity towards boron and resulted in 79-93% boron removal even in the presence of competing metal ions (Na+ and Cr2+). Experiments were performed in a column system, and breakthrough time was observed to increase with bed depths and decreased with flow rates. The batch experiments revealed that 60 min was enough to achieve equilibrium, and the level of boron sorption was 108.5 mg/g from a synthetic solution. Several adsorption desorption cycles were performed using a simple acid water treatment and evaluated using various kinetic models. The spent adsorbents could be separated easily from the mixture by an external magnetic field. The cost-benefit analysis was performed for the treatment of 72 m(3)/year boron effluent, including five years straight line depreciation charges of equipment. The net profit and standard percentage confirmed that the recovery process is economically feasible. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Techno-economic analysis; Boron-selective adsorbents; Hybrid materials; Porous magnetic adsorbents; Boric acid recovery; Fixed-bed studies